The Effects of Principal Leadership on Work Motivation and Performance of Teachers to Improve the Learning Outcomes on Science of the Fifth Grade Students of SD Tojo Una-Una Regency - Saiyan, Kamir Apoka; Rede, Amram; Abram , Paulus Hengky (Universitas Tadulako, 2018)
The study aimed to determine whether there is an influence between the principal leadership on the learning outcomes on the science of the fifth-grade students of SD Tojo Una-Una Regency and to improve performance of teachers in improving learning outcomes on the science of the fifth-grade students of SD Tojo Una-Una Regency. This study used a type of quantitative research. The instruments in this study were a questionnaire sheet. The instrument test used Validity Test and Reliability Test. The data analysis technique used the t-test technique which is preceded by an analysis prerequisite test, namely the normality test and linearity test.Â P-value results of the normality test on the principal's leadership value (0.28)> 0.05 and student learning outcomes (0.17)> 0.05. thus, the data obtained were normally distributed. Therefore, the principal leadership can influence work motivation and performance of teachers, so that student learning outcomes also increase.